Air pollution and sports performance in Beijing - Lippi, G.; Guidi, G. C.; Maffulli, N. (International Journal of Sports Medicine, 2008)
The Beijing Olympics will begin in August 2008 and athletes will face an unpredictable challenge. Based on present data, Beijing is one of the most polluted megacities in the world; the air concentrations of carbon monoxide (CO), ozone, nitrogen oxides (NO and NO2), sulphur dioxide (SO2) and particulate matter approach or exceed the current limits established by U.?S. Environmental Protection Agency (EPA). Although the athletes who will be competing in Beijing are physiologically very different to the participants in most published studies, and it is therefore difficult to predict individual responses, there is little doubt that the presence of these air pollutants might be detrimental to athletic performance due to the marked increase (up to 20-fold) in ventilatory rate and concomitant nasal and oral breathing. Moreover, mouth breathing often bypasses the noise during strenuous exercise, increasing the deleterious effects of pollutants on health and athletic performance. Although limited, each decrement in athletic performance would have a potentially deleterious impact on top-class athletes competing in the next Olympics in China. Several Olympic records are regularly broken during the Olympics. Will this be the case for Beijing?